Case Report and Literature Review: Ectopic Thyrotropin-Secreting Pituitary Adenoma in the Suprasellar Region - Li, Xiaoxu; Zhao, Binghao; Hou, Bo; Wang, Jing; Zhu, Jianyu; Yao, Yong; Lian, Xiaolan (Frontiers in Endocrinology, 2021)
Ectopic thyrotropin-secreting pituitary adenoma (ectopic TSH-oma) is a rare disorder that is easily misdiagnosed in clinical work. We report one patient who presented with hyperthyroidism and a suprasellar mass. In this case, preoperative diagnosis of suprasellar ectopic thyrotropin-secreting pituitary adenoma was challenging. A literature review revealed that a total of 11 patients with ectopic TSH-oma were previously reported, and only our one case was diagnosed in the microadenoma stage. Most of the patients with TSH-oma or ectopic TSH-oma were middle-aged. We described ectopic TSH-oma in a child at length. We recommend that ectopic TSH-oma should be considered in the differential diagnosis of thyrotoxicosis syndrome to achieve an accurate, early diagnosis. The somatostatin suppression test and imaging examinations, such as magnetic resonance imaging and positron emission tomography/magnetic resonance imaging, could contribute to the diagnosis. Once the diagnosis was highly suspected, tumor resection could achieve a satisfying long-term outcome in ectopic TSH-oma.